1977
DOI: 10.1007/bf01909593
|View full text |Cite
|
Sign up to set email alerts
|

Thermal investigations on the crystallization of sorbitol

Abstract: The melting and crystallization of sorbitol were investigated with the DSC method and thermal microscopy. Sorbitol was found to have two crystalline modifications (confirmed by X-ray diffraction) with different melting points, while rapid cooling of molten sorbitol resulted in an amorphous form.The effect of inoculation on the crystallization of the melt was studied too. Powders of both crystalline modifications were used for this purpose.A new technological process for rapid crystallization of molten sorbitol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…Melting at 120 1C and quenching with liquid nitrogen has been reported by Cammenga and Steppuhn [6], but this can lead to an uncontrolled rate of cooling, with crystallisation taking hours to days [5,7].…”
Section: The Crystallised Melt (E 0 and E)mentioning
confidence: 96%
See 3 more Smart Citations
“…Melting at 120 1C and quenching with liquid nitrogen has been reported by Cammenga and Steppuhn [6], but this can lead to an uncontrolled rate of cooling, with crystallisation taking hours to days [5,7].…”
Section: The Crystallised Melt (E 0 and E)mentioning
confidence: 96%
“…Hales (cited in [3]) described the form as ''glass transition product E'' while Sztatisz et al [5] mentioned ''frozen melt'' or ''molten sorbitol''. These authors have reported DSC runs of sorbitol after melting and storage for some hours after cooling to room temperature.…”
Section: The Crystallised Melt (E 0 and E)mentioning
confidence: 98%
See 2 more Smart Citations
“…A literature search thereafter revealed that D-sorbitol has two crystalline forms, as indicated by calorimetry and x-ray diffraction. 40 Since some of the unusual findings in an earlier study may have been caused by crystallization, it seemed necessary also to study the ⑀Ј and ⑀Љ spectra of D-sorbitol by avoiding its crystallization and by repeated measurements. Here we report a detailed study of the Johari-Goldstein relaxation in D-sorbitol glass obtained by cooling at different rates, and of the change in its characteristics with time and with temperature.…”
Section: Introductionmentioning
confidence: 99%